2021
DOI: 10.1002/solr.202100191
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographically Oriented Hybrid Perovskites via Thermal Vacuum Codeposition

Abstract: Hybrid lead halide perovskites typically form polycrystalline films that have multiple grain sizes and surface defects. A key engineering challenge toward commercialization is therefore the production of homogeneous, defect‐free large‐area devices achieving high efficiency. New market opportunities may arise from vacuum‐deposited perovskites if detailed understanding and control of crystal formation are available. Of the many factors that make reproducibility of device performance difficult, two variables are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…To obtain a more in-depth insight into the molecular stacking of PBZ-Si polymers, the angular dependence of the diffraction peak at q z ∼1.75 Å −1 was examined. 68 The intensity of the peak became significantly higher at ∼80° for the sample of ITO/SnO 2 /perovskite/PBZ-3Si (Fig. S7b†), indicating a similarly well-aligned PBZ-3Si polymer to the sample of Si/PBZ-3Si (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…To obtain a more in-depth insight into the molecular stacking of PBZ-Si polymers, the angular dependence of the diffraction peak at q z ∼1.75 Å −1 was examined. 68 The intensity of the peak became significantly higher at ∼80° for the sample of ITO/SnO 2 /perovskite/PBZ-3Si (Fig. S7b†), indicating a similarly well-aligned PBZ-3Si polymer to the sample of Si/PBZ-3Si (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…We have described a positive effect MeO-groups on the perovskite crystallization, leading to micrometer-sized crystal features. [37] nm than the grains on MoO3/Spiro-OMeTAD (~333 nm). On SnO2 and MeO-2PACz, the perovskite grains showed a larger average size (~455nm and ~404nm) and can be easily distinguished by their grain-like features.…”
Section: Morphology and Crystallization Of Thin Filmsmentioning
confidence: 84%
“…reported that the chemical groups of underlayer influence the perovskite formation and stability, [37] we, therefore, investigated the formation of the perovskite layer on different organic materials. We extended our study to the state-of-the-art used underlayers.…”
Section: Morphology and Crystallization Of Thin Filmsmentioning
confidence: 99%
See 2 more Smart Citations